The Influence Of Competence, Leadership Style, And Career Development On Performance Employee Bps West Java - Zarkasi Zarkasi (Program Pascasarjana STIE Amkop Makassar, 2023)
This study aims to determine and analyze the influence of competence, leadership style and career development, on the performance of BPS employees throughout West Java. Population in this research is a number 133 person, with sample study as much 99 employee. Technique taking sample is simple random sampling. Data obtained through the distribution of questionnaires and data analysis with analysis regression linear double. Results study disclose that competence, style leadership and career development have a positive and significant effect on employee performance. Matter this shows that to improve employee performance, it is necessary to increase competence, style leadership And development career. Between third variable the, competence is variable Which most influential to performance employee. Matter This seen from mark standardized competency coefficients of 0.460. This is due to competence as an individual internal factor which can be controlled by the individual himself. The research results also show that performance affected employees as big 41.7% by competence, style leadership And development career in a manner together. Meanwhile for the rest as big 56.1% is influence factor other Which No entered to in study This. Keywords: Competence; Style Leadership; Development Career; Performance